'Underground' rap performance, informality and cultural production in Dar es Salaam. (1st March 2015) - Kerr, David
Hip hop is part of a global economy of music, images and signs. Since the 1990s, hip hop has become an increasingly mainstream part of the African musical landscape. In Tanzania, as hip hop has become progressively more popular, the practice of rapping has also become more widespread. In recent years, Dar es Salaam has seen a growth in andagraundi or 'underground' rappers. It is, in part, through the consumption of transnational styles and signs that underground rappers are able to fashion themselves. Through popular cultural practice, rappers embody the transnational persona of a rapper. These transnational ideas and symbols are, however, imbued with meanings embedded in local discourses. The distinction frequently made between the local and the global is collapsed by the rappers as they come to embody the local in the global and vice versa.